2005
DOI: 10.1007/s10528-005-5212-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Blastocerus dichotomus Populations in the Paraná River Basin (Brazil) Based on Protein Variability

Abstract: The population structure of 147 marsh deer (Blastocerus dichotomus) from three areas in the Paraná River basin, Brazil, was studied by observing protein polymorphism at 17 loci. Six loci were polymorphic and 11 monomorphic. The proportion of polymorphic loci (P) was 35.29% and the average heterozygosity (H) was 6.31%. Wright's FST indicated that only 4.9% of the total variation in allelic frequencies was due to genetic differences between the three groups. The high value of F(IS) (0.246) indicated inbreeding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…As in some neotropical deer species, the sex dispersal rate is unbiased, since females are frequently phylopatric and have a low dispersal rate [Cathey et al, 1998;González et al, 1998;Randi et al, 1998;Purdue et al, 2000;Oliveira et al, 2005;Márquez et al, 2006]. The cytogenetic analysis, representing nuclear inheritance, can complement the mutation rate to analyze, understand and elucidate the 'red brocket deer complex' evolution.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…As in some neotropical deer species, the sex dispersal rate is unbiased, since females are frequently phylopatric and have a low dispersal rate [Cathey et al, 1998;González et al, 1998;Randi et al, 1998;Purdue et al, 2000;Oliveira et al, 2005;Márquez et al, 2006]. The cytogenetic analysis, representing nuclear inheritance, can complement the mutation rate to analyze, understand and elucidate the 'red brocket deer complex' evolution.…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
“…Nuclear DNA studies using allozymes and microsatellite loci in a sample of individuals from Porto Primavera showed that this population had low levels of polymorphism (Garcı´a and Duarte 2001;Oliveira et al 2005) and cytogenetic studies showed that the marsh deer had no karyotypic variation (Bogenberger et al 1987;Duarte and Giannoni 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the marsh deer a high rate of mortality (50%) was observed, as well as a slow recuperation of the population. The latter could be related to inbreeding (De Oliveira et al, 2005), because these deer constitute an isolated group with little possibility of maintaining contact with other populations. These observations suggest that rabies transmitted by vampire bats could constitute a threat to the survival of marsh deer, especially in those places where reproductive success is normally limited, as occurs in some parts of Argentina (Mares et al, 1989;Dellafiore and Maciera, 1998) and Brazil (Schaller and Vasconcelos, 1978).…”
mentioning
confidence: 99%